DEVELOPMENT OF AN EDUCATIONAL ANIMATED VIDEO ON EXHAUST EMISSIONS FOR AUTOMOTIVE VOCATIONAL SCHOOL STUDENTS (ATIKANOTO: Journal of Automotive Engineering Education, 2025)
This study aims to develop an educational animation video on exhaust gas emissions as a learning medium for vocational high school students in the Automotive Engineering program. The research applied a development method using the Analysis, Design, Development, Implementation, Evaluation (ADDIE) model up to the formative evaluation stage. A questionnaire based on the Learning Object Review Instrument (LORI) was used to assess validity, practicality, and potential effectiveness. The research subjects consisted of expert validators and users who provided assessments through a feasibility test. The results of expert validation showed an average score of 4.575 out of 5, categorized as highly feasible, while user assessments gave positive responses regarding content accuracy, curriculum alignment, presentation design, and visual appeal. Based on these findings, the developed educational animation video was declared feasible for use in automotive engineering learning and has the potential to enhance students’ understanding and motivation in studying the topic of exhaust gas emissions. Penelitian ini bertujuan mengembangkan video animasi edukatif tentang emisi gas buang sebagai media pembelajaran bagi murid Sekolah Menengah Kejuruan Teknik Otomotif. Penelitian menggunakan metode pengembangan dengan model Analysis, Design, Development, Implementation, Evaluation (ADDIE) hingga tahap evaluasi formatif. Instrumen berupa angket berbasis Learning Object Review Instrument (LORI) digunakan untuk menilai validitas, kepraktisan, dan potensi efektivitas. Subjek penelitian terdiri atas validator ahli dan pengguna yang menilai melalui uji kelayakan. Hasil validasi ahli menunjukkan rata-rata skor 4,575 dari 5 dengan kategori sangat layak, sedangkan penilaian pengguna memberikan respons positif pada aspek keakuratan materi, kesesuaian kurikulum, desain penyajian, dan daya tarik visual. Berdasarkan temuan tersebut, video animasi edukatif yang dikembangkan dinyatakan layak digunakan dalam pembelajaran teknik otomotif serta berpotensi meningkatkan pemahaman dan motivasi murid terhadap topik emisi gas buang.